Multicentered Study Evaluating Pharmacy Students' Perception of Palliative Care and Clinical Reasoning Using Script Concordance Testing. (November 2018) - Atayee, Rabia S.; Lockman, Kashelle; Brock, Cara; Abazia, Daniel T.; Brooks, Tracy L.; Pawasauskas, Jayne; Edmonds, Kyle P.; Herndon, Christopher M.
Introduction: As the role of the pharmacist on the transdisciplinary palliative care team grows, the need for adequate instruction on palliative care and clinical reasoning skills in schools of pharmacy grows accordingly. Methods: This study evaluates second- and third-year pharmacy students from 6 accredited schools of pharmacy that participated in surveys before and after the delivery of a didactic palliative care elective. The survey collected student demographics, perceptions of the importance of and student skill level in palliative care topics. The script concordance test (SCT) was used to assess clinical decision-making skills on patient cases. Student scores on the SCT were compared to those of a reference panel of experts. Results: A total of 89 students completed the pre-/postsurveys and were included in data analysis. There was no statistically significant difference in student perceived importance of palliative care skills before and after the elective. Students from all 6 institutions showed significant increase in confidence in their palliative care skills at the end of the course. There was also a significant improvement across all institutions in clinical reasoning skills in most of the SCT questions used to assess these skills. Conclusions: Students choosing an elective in palliative care likely do so because they already have an understanding of the importance of these topics in their future practice settings. Delivery of a palliative care elective in the pharmacy curriculum significantly increases both student confidence in their palliative care skills and their clinical reasoning skills in these areas.